ESG Ratings and the Performance of Socially Responsible Mutual Funds: A Panel Study - Nandita Das; Swarn Chatterje; Bernadette Ruf; Aman Sunder (Journal of Finance Issues, 2018)
This study uses the Fama-French 5-factor model to examine the risk-adjusted performances of Socially Responsible Mutual Funds (SRMF) relative to the market over a 12-year (2005–2016) period. The timeframe of this study overlaps the periods leading up to, during, and immediately past the Great Recession. This study also examines whether the Environmental, Social, and Governance (ESG) ratings assigned to the SRMF signal fund performance over time. The results indicate that although the SRMF underperformed in the market during the 2005–2016 period, there was no difference in the SRMF performance with respect to the market during the Great Recession period. Furthermore, our results indicate that the SRMF with higher ESG ratings outperformed the SRMF with lower ESG ratings during the Great Recession period. Implications of this study's findings for investment analysts, portfolio managers, and financial planners are included.
Keywords: E22; E27; G11; M14; 330; Quantitative Finance; Mutual Funds and ETFs; Socially Responsible Investing (SRI); ESG Ratings; Fund Performance; Risk Premium; Investment Decisions; Portfolio Performance